Pertanggungjawaban Pelaku Usaha Terhadap Pengoplosan Bahan Bakar Minyak Pertalite Perspektif At-Tadlis Mazhab Maliki: Studi Kasus SPBU No.14.201.135 Kelurahan Tanjung Selamat - Anwar Pardomuan Simarmata; Muhammad Amar Adly (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The practice of fuel adulteration (BBM) is a form of fraud in energy trading activities that can harm consumers and violate applicable legal provisions. The case of Pertalite fuel adulteration that occurred at the Nagalan Berkah Bersama Gas Station No. 14.201.135 in Tanjung Selamat Village, Medan City, has attracted attention because it is suspected to have been carried out by mixing Pertalite with an octane rating of RON 90 with lower octane gasoline, thereby reducing the quality of the fuel sold to consumers. This study aims to analyze the form of fuel adulteration practices and the liability of business actors for consumer losses in terms of positive Indonesian law and the at-tadlīs perspective in the Maliki School of Law. The research method used is empirical juridical research with a living case study approach, statute approach, and conceptual approach. Data were obtained through interviews, document studies, and reviews of laws and regulations and muamalah fiqh literature. The results of the study indicate that the practice of fuel adulteration is carried out by mixing Pertalite with lower octane gasoline to obtain illegal profits. Under Indonesian positive law, this action violates Law Number 22 of 2001 concerning Oil and Gas and Law Number 8 of 1999 concerning Consumer Protection, thus subjecting business actors to criminal and civil liability, including the obligation to provide compensation to consumers. Meanwhile, from the perspective of the Maliki School, this practice is categorized as a form of at-tadlīs, namely fraud in transactions by concealing or manipulating the quality of the goods being traded. Therefore, business actors are obliged to provide compensation (dhamān) for the losses incurred and may be subject to ta'zīr sanctions by the competent authorities to maintain justice and the welfare of economic activities.